Perceived training load, muscle soreness, stress, fatigue, and sleep quality in professional basketball: A full season study - Clemente, F. M.; Mendes, B.; da Glória Teles Bredt, S.; Moreira Praça, G.; Silvério, A.; Carriço, S.; Duarte, E. (Journal of Human Kinetics, 2019)
This study aimed to compare the perceived training load (session-RPE) and wellness status (muscle soreness, stress, fatigue, and sleep quality) within and between regular (one-match) and congested (two matches) weeks. Fifteen professional basketball players from a European First league club participated in this study. Wellness status (Hooper`s questionnaire) and perceived training loads (session-RPE) were measured for each training session and matches over a full season. Regular weeks presented moderately greater session-RPE than congested weeks (p = 0.201; d = 2.15, moderate effect). Both regular and congested weeks presented a decrease in perceived training load before matches, which was accompanied by improved wellness status on a match day. Congested weeks presented moderately lower sleep quality (p = 0.421; d = 1.320, moderate effect) and moderately greater fatigue (p = 0.468; d = 1.401, moderate effect) than regular weeks. Regular and congested weeks presented minimum differences for DOMS and stress. Lower wellness in congested weeks may be associated to an accumulative effect of training and match loads. Tapering phases before matches seem to play an important role for improving athletes` wellness and preventing overtraining. Keywords: training monitoring; load, well-being; basketball; congested fixture Introduction